ANALYSIS OF COST AND TIME FOR THE COMPLETION OF THE MAINTENANCE PROJECT OF THE KARETAN – SAMBIMULYO ROAD IN BANYUWANGI REGENCY - Oscar Harris; Risma Marleno; Wateno Oetomo (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Along with technological developments in the field of project work implementation, it must also be accompanied by developments in the field of Management as a control function in the implementation of the project. In this case, the application of the Earned Value Concept Method is expected to be able to provide an alternative solution to the problem of evaluating the cost and time that has been spent on project implementation. The purpose of this research is to evaluate a project work that is being done, namely in the form of Maintenance of KaretanSambimulyo Road, Banyuwangi Regency against Project Time and Cost Control, so that it can be used as a reference material by the project implementer and the employer in terms of decision making whether the project is feasible to complete or not. The research was conducted at the end of week 21 (twenty-one), with different evaluation results, thus it can be concluded with the following description: a. Based on Cost Variance (CV) & Schedule Variance (SV) analysis results obtained: Work is carried out later than the schedule plan, costs are lower than the budget plan; b. Based on Cost Performance Index (CPI) & Schedule Performance Index (SPI): Profit but experiencing delays; c. Based on Estimation to Complete (ETC) & Estimation at Completion (EAC): Obtaining a profit of Rp. 263,004,000, 00-,; d. Based on Estimate Temporary Cost (ETC) & Estimate All Cost (EAS): Experienced a Time Delay of 2.09 Weeks